ZAHIRIDDIN MUHAMMAD BABUR-GREAT ADIB AND POET, ENLIGHTENED SCHOLAR, GREAT DAVLAR FIGURE - Inoyatov Qutlug’jon Hamdamovich (Journal Park Publishing, 2023)
This article describes the life and work of Zahiriddin Muhammad Babur,his works related to his pen, his discoveries on creativity, improvement,development of kasbu craft and agriculture, pandu exhortations on raising children, as well as studies conducted by our respubik and foreign scientists and their comparative analysis
Keywords: Umar Sheikh Mirzo, Crown Prince, Z.M.Babur, Akhsi, Andijan